Killing Two Birds with One Stone: KPU in Passing the Political Turbulence of Identity and The Leap of Millenial Young Voters - Dian - Fitriyani; Priyatno - Harsasto (Journal of Politic and Government Studies, 2020)
Election 2019 is a special election because of the high participation of 81 percent and tinged the very hard competition of two presidential candidates and vice presidents. According to Hasyim Asyari, the commissioner of KPU RI 2017/2022 and some of the observers ' opinion increase in participation is due to the versatility of the implementation between legislative elections from local to national level and presidential election/vice president. This research uses qualitative descriptive methods with data collection techniques in the form of interviews and documentation. Data is then analyzed using theory and data sources to answer the question of increasing participation and role of KPU in encouraging honest, fair, and safe elections. Contrary to the opinion of observers, the study found that increased participation was caused more by the fairhouse of falsehood, head to head of jokowi and prabowo in 2014, young millennium voters spikes, and volunteer roles. The fierce competition between the supporters of both candidates can be overcome by KPU by putting themselves as a national, permanent and independent institution, performing socialization targeting the entire population and the turn back hoax movement to ward off the election hoax. Moreover, the election commission was assisted by community volunteers to control the elections and thus produce legitimized elections. The conclusion that can be withdrawn from this research is KPU managed to perform its duties well, besides being able to utilize the momentum to increase participation and able to dampen the conflict among the electoral participants and produce a reliable elections. The KPU works in accordance with the prevailing rules, neutral, and socializing to the fullest extent possible to keep it as an electoral organizer until Indonesia's democracy is maintained as it should.